Intruders Versus Intrusiveness: Teens' and Parents' Perspectives on Home-Entryway Surveillance - Ur, Blase; Jung, Jaeyeon; Schechter, Stuart (2014 ACM International Joint Conference on Pervasive and Ubiquitous Computing (UbiComp 2014), 2014)
We investigated how household deployment of Internetconnected locks and security cameras could impact teenagers’ privacy. In interviews with 13 teenagers and 11 parents, we investigated reactions to audit logs of family members’ comings and goings. All parents wanted audit logs with photographs, whereas most teenagers preferred text-only logs or no logs at all. We unpack these attitudes by examining participants’ parenting philosophies, concerns, and current monitoring practices. In a follow-up online study, 19 parents configured an Internet-connected lock and camera system they thought might be deployed in their home. All 19 participants chose to monitor their children either through unrestricted access to logs or through real-time notifications of access. We discuss directions for auditing interfaces that could improve home security without impacting privacy.
Best Paper